Imaging of Endoplasmic Reticulum Ca2+ in the Intact Pituitary Gland of Transgenic Mice Expressing a Low Affinity Ca2+ Indicator - Rojo-Ruiz, Jonathan; Navas-Navarro, Paloma; Nuñez, Lucía; García-Sancho, Javier; Alonso, María Teresa (Frontiers in Endocrinology, 2021)
The adenohypophysis contains five secretory cell types (somatotrophs, lactotrophs, thyrotrophs, corticotrophs, and gonadotrophs), each secreting a different hormone, and controlled by different hypothalamic releasing hormones (HRHs). Exocytic secretion is regulated by cytosolic Ca2+ signals ([Ca2+]C), which can be generated either by Ca2+ entry through the plasma membrane and/or by Ca2+ release from the endoplasmic reticulum (ER). In addition, Ca2+ entry signals can eventually be amplified by ER release via calcium-induced calcium release (CICR). We have investigated the contribution of ER Ca2+ release to the action of physiological agonists in pituitary gland. Changes of [Ca2+] in the ER ([Ca2+]ER) were measured with the genetically encoded low-affinity Ca2+ sensor GAP3 targeted to the ER. We used a transgenic mouse strain that expressed erGAP3 driven by a ubiquitous promoter. Virtually all the pituitary cells were positive for the sensor. In order to mimick the physiological environment, intact pituitary glands or acute slices from the transgenic mouse were used to image [Ca2+]ER. [Ca2+]C was measured simultaneously with Rhod-2. Luteinizing hormone-releasing hormone (LHRH) or thyrotropin releasing hormone (TRH), two agonists known to elicit intracellular Ca2+ mobilization, provoked robust decreases of [Ca2+]ER and concomitant rises of [Ca2+]C. A smaller fraction of cells responded to thyrotropin releasing hormone (TRH). By contrast, depolarization with high K+ triggered a rise of [Ca2+]C without a decrease of [Ca2+]ER, indicating that the calcium-induced calcium-release (CICR) via ryanodine receptor amplification mechanism is not present in these cells. Our results show the potential of transgenic ER Ca2+ indicators as novel tools to explore intraorganellar Ca2+ dynamics in pituitary gland in situ.